2016
DOI: 10.1136/thoraxjnl-2016-209512
|View full text |Cite
|
Sign up to set email alerts
|

Androgen deprivation therapy for prostate cancer and the risk of hospitalisation for community-acquired pneumonia

Abstract: The use of ADT is associated with an increased risk of hospitalisation for community-acquired pneumonia in men with prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…By regulating cellar proliferation or survival, AR negatively regulates the number of alveolar macrophages (AM) to reduce the recruitment of inflammatory factors in the lung [63]. Given the AR receptor knocked out, the human body would be more susceptible to microbial, thus the risk of hospitalization for pneumonia would increase [64]. In addition, these major hub genes all had great binding capacity to the key compounds by molecular docking verification.…”
Section: Discussionmentioning
confidence: 99%
“…By regulating cellar proliferation or survival, AR negatively regulates the number of alveolar macrophages (AM) to reduce the recruitment of inflammatory factors in the lung [63]. Given the AR receptor knocked out, the human body would be more susceptible to microbial, thus the risk of hospitalization for pneumonia would increase [64]. In addition, these major hub genes all had great binding capacity to the key compounds by molecular docking verification.…”
Section: Discussionmentioning
confidence: 99%
“…ADT is an important treatment modality for patients with prostate cancer, and several studies have demonstrated an increased risk of pneumonia in patients with prostate cancer who receive gonadotropin-releasing hormone. [15][16][17] A population-based cohort study using data from the UK Clinical Practice Research Datalink linked to the Hospital Episode Statistics repository assessed 20,310 men newly diagnosed with nonmetastatic prostate cancer and demonstrated that current ADT treatment was associated with a higher risk of hospitalization for community-acquired pneumonia. 17 Several Figure 3.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] A population-based cohort study using data from the UK Clinical Practice Research Datalink linked to the Hospital Episode Statistics repository assessed 20,310 men newly diagnosed with nonmetastatic prostate cancer and demonstrated that current ADT treatment was associated with a higher risk of hospitalization for community-acquired pneumonia. 17 Several Figure 3. Kaplan-Meier survival curves are illustrated for elderly patients with prostate cancer who did and did not receive the 23-valent pneumococcal polysaccharide vaccine (PPSV23) (log-rank test; P = .0003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Thorax , Hicks et al 9 carried out a large-scale, population-based study of UK men with newly diagnosed non-metastatic prostate cancer between 1998 and 2015. They used data obtained from electronic healthcare records to comprehensively measure the risk of hospitalisation for CAP, comparing patients currently being treated with ADT, or patients who had past ADT use, to patients who had never received ADT.…”
mentioning
confidence: 99%